Measuring Prevalence of Burnout among Nurses in Hospital Ward - Zunaedi, Rosly (Universitas Tribhuwana Tunggadewi, 2024)
Burnout is a phenomenon commonly found in nurses, arising from chronic work fatigue. It is a detrimental and impactful syndrome that affects not only the individual, but also the organization and the patients. This study aims to determine the prevalence of burnout syndrome in nurses working in hospital wards. The research design used is descriptive quantitative. The population in this study comprises 78 nurses who worked in the inpatient room of a private hospital in Malang Regency. The sampling technique used was total sampling. Data were collected using the MBI (Maslach Burnout Inventory) questionnaire which contains 22 items designed to assess burnout symptoms in health workers. The MBI measures three indicators of burnout: emotional exhaustion, depersonalization, and reduced personal accomplishment. The value ranges for low, medium, and high risk are 0–18, 19–26, and 26 for emotional exhaustion; 0–5, 6–9, 9 for depersonalization; and 0-33, 34–39, 39 for reduced personal accomplishment. Burnout is determined if emotional exhaustion and Depersonalization are both